The Translation Analysis of Strategies and Qualities of Onomatopoeic Verb in ROOM Novel - Nadiyah, Azmi (Universitas Sebelas Maret, 2022)
AbstractThis research studied the onomatopoeic verb in Emma Donoghue’s novel entitled ROOM. The aims of this research were to find the translation strategies applied in translating onomatopoeic verbs that are used by the translator in the ROOM novel and to assess their quality in terms of accuracy and acceptability. This research applied descriptive qualitative method where the data was analyzed through Baker’s theory and those called raters who have competencies in assessing translation quality. The approaches used to collect and analyze the data of onomatopoeic verbs were content analysis and Focus Group Discussion. As a result, the researchers found that there are five translation strategies that are applied in translating onomatopoeic verbs. The researchers concluded that the majority of the translation strategies used in the ROOM novel involve the use of non-onomatopoeic words with similar meaning and form. The translation quality of onomatopoeic verbs is rated as less accurate and less acceptable, because of various factors that may be read in depth in this article.